Technique for transcarotid artery revascularization of tandem lesions - Magee, Gregory A. (J Vasc Surg Cases Innov Tech, 2021)
The repair of tandem carotid lesions has been described using myriad methods, often involving a hybrid approach of stenting with carotid endarterectomy. Because of the worrisome stroke rates associated with this method, we have reported an innovative technique of transcarotid artery revascularization (TCAR) for tandem lesions in a patient with high-grade stenosis of the right common and internal carotid arteries. Technical success was achieved with TCAR via retrograde and antegrade access using dynamic flow reversal for the treatment of both lesions. The patient experienced no postoperative complications, highlighting the successful repair of tandem carotid lesions using TCAR in a patient who is too high risk for carotid endarterectomy.